Medical image processing and analysis and telemedicine - Biomedical engineering research centre, NTU. (2008)
The report contains three parts. The first part deals with telemedicine, and in particular processing of electrcardiographic signals for transmission and analysis. This paper also reports the use of a program to complement the ECG data transmission process. The program includes an algorithm to detect and analyze ECG waveforms from a stream of ECG data stored in a medical control module (MCM) attached to the ECG machine. A paper presented at the symposium at SGH on electrocardiograph transmission and analysis in Ambulance-Hospital telemedicine studies is given in Chapter 2. In Chapter 3, a paper on multimode communication links for patient information is presented. In the second part, the response of functionally adapted dentine to temperature changes in physiological range is analyzed using a Digital Speckle Pattern Interferometer (DSPI) and thermography in conjunction with an advanced digital fringe processing technique. The third part deals with medical image processing and analysis of esophageal images for preliminary diagnosis of cancer are mostly performed qualitatively by the physician, which is time-consuming, subject to a lot of variations in interpretation and not very suitable for quantitative analysis and comparative evaluation. These limitations can be alleviated by computer-based image processing and analysis.